Review of bioresource-based conductive composites for portable flexible electronic devices - Mahalingam S. (Elsevier Ltd, 2025)
Recent advances in portable electronics, such as foldable displays, smart clothing, and synthetic skins, have revealed new applications for everyday life. The high dependency on portable electronic devices in humankind's daily routine has raised the consumer's awareness of environmental and sustainability issues. These portable electronic devices commonly use non-renewable polymeric materials mainly obtained from petroleum and are a primary environmental concern. Hence, bioresource materials from renewable sources are biodegradable and have no adverse environmental effects. Mainly, biopolymers have recently emerged as a promising path in portable electronic devices due to their compliance with roll-to-roll processing, flexibility, and lightweight. However, the drawback of biopolymers compared to synthetic polymers is their inherent insulation properties. In order to increase the conductivity of biopolymers, incorporating them with conductive material is an excellent method. These biopolymer-based conductive composites possess outstanding electrical conductivity and mechanical properties. This review focuses on the recent advancements in flexible biopolymer-based conductive composites used in portable electronics such as energy storage, self-powered, and wearable sensors and devices. A detailed review of the type of flexible biopolymer-based conductive composites, such as fiber, film, gel, and cloth, is highlighted for each electronic device. The development of flexible biopolymer-based conductive composites was mainly used in energy storage devices, whereas self-powered devices had the least product developed. The wearable performance of these portable electronics was influential in the sustainability and reliability of these devices to be used in daily human activities. ? 2023 Elsevier Ltd